Narratives of gang desistance amongst former gang members - Kelly, Jane Frances (2019)
Gangs are found all over the world, including South Africa. In Cape Town specifically, gang involvement is a critical problem in need of intervention. Despite this, little research has explored the perspectives of former gang members on leaving and staying out of the gang. Understanding how and why individuals desist from gangs has important implications for policymakers, the criminal justice system, and in the development of effective interventions, which is particularly important in low- and middle-income countries like South Africa, where very little is known about desistance from gangs, and where economic and other conditions that may lead to gang involvement are different from those in high-income countries. Drawing on a narrative theoretical framework as well as the theory of critical realism, this research sought to examine how former South African gang members understand and make sense of their desistance from gang involvement, focusing on exiting the gang life as well as maintaining a reformed lifestyle after exiting, despite the challenges this may present. Two rounds of life history interviews were conducted with twelve former gang members from a Cape Town community with a high prevalence of gangsterism. Thematic narrative analysis was used to analyse the interview data. Findings revealed that the participants’ narratives of desistance focused on a profound transformation in identity in which they moved away from the hardened, stoic gangster identity and embraced a more prosocial identity, such as that of a positive role model in the community. This transformation was a process punctuated with key turning points (such as incarceration or becoming religious) that prompted active reflection on the gang life and contributed to their decision to desist. The participants’ narratives also focused on their agency in the desistance process, which included forming a purposive intention to change their lives, committing to and maintaining this change, in spite of challenges they faced (for example, a relapse into drugs), taking personal responsibility for their pasts and striving for more independence in the future. Importantly, it also involved actively drawing on protective resources (such as meaningful and practical support from loved ones and religious belief systems) and prosocial identities (for example, being a caring husband and father) available to them within their environments, thus illustrating how the desistance process is an interaction between inner and outer resources. Therefore, it is imperative that interventions that assist desisting gangsters are targeted not only on an individual level, but a contextual level too, ensuring that individuals have access to the kinds of resources in their environment that will support their desistance